1998
DOI: 10.1177/026119299802602s02
|View full text |Cite
|
Sign up to set email alerts
|

MEIC Evaluation of Acute Systemic Toxicity

Abstract: The Multicenter Evaluation of In Vitro Cytotoxicity (MEIC) programme was set up to evaluate the relevance for acute human systemic toxicity of in vitro cytotoxicity tests. At the end of the programme in the summer of 1996, 29 laboratories had tested all 50 reference chemicals in 61 cytotoxicity assays. As a necessary prerequisite to the forthcoming evaluation papers of this series, this paper presents the animal and human toxicity data of the programme. This database contains tabulated handbook data for the 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It was shown in the MEIC study that, for 50 reference chemicals (9), average IC50 values from ten 24-hour exposure tests with human cell lines predicted human peak blood concentrations from LC50 curves better (R 2 = 0.74; Figure 1) than the prediction of human lethal doses by LD50 values for rats and mice (R 2 = 0.60-0.66). Furthermore, the accuracy of the prediction of human lethal concentrations increased considerably, if known human kinetic data, such as knowledge of the passage across the blood-brain barrier (BBB) and the timing of the lethal action, were used together with the cytotoxic concentrations obtained in the cell line assays.…”
Section: The Meic and Edit Projectsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was shown in the MEIC study that, for 50 reference chemicals (9), average IC50 values from ten 24-hour exposure tests with human cell lines predicted human peak blood concentrations from LC50 curves better (R 2 = 0.74; Figure 1) than the prediction of human lethal doses by LD50 values for rats and mice (R 2 = 0.60-0.66). Furthermore, the accuracy of the prediction of human lethal concentrations increased considerably, if known human kinetic data, such as knowledge of the passage across the blood-brain barrier (BBB) and the timing of the lethal action, were used together with the cytotoxic concentrations obtained in the cell line assays.…”
Section: The Meic and Edit Projectsmentioning
confidence: 98%
“…Several studies have shown good correlations (over 70%) between in vitro basal cytotoxicity data (the 50% inhibitory concentration [IC50]) and rodent LD50 values (see Halle's Registry of Cytotoxicity [1]) or human lethal blood concentrations (see the MEIC study [2,3]). In the MEIC study, the relevance of using in vitro toxicity tests for predicting human acute systemic toxicity was evaluated under the management of Björn Ekwall (2)(3)(4)(5)(6)(7)(8)(9).…”
Section: Previous Studies On Acute Systemic Toxicitymentioning
confidence: 99%
“…The MEIC programme was a seven-year study, in which 59 laboratories worldwide, tested 50 reference chemicals selected by the Swedish Poison Information Centre, and obtained from various sources, according to in-house protocols (14). Information about human toxicity and kinetics from drug/chemical overdoses was available for each chemical, from which 50% lethal blood concentrations (LC50) were derived (15). These LC50s were compared with in vitro data produced via the testing laboratories.…”
Section: The Rationale For Using Basal Cytotoxicitymentioning
confidence: 99%
“…It was designed to evaluate the relevance of in vitro cytotoxicity tests for predicting human acute systemic toxicity and to select the best combination of in vitro toxicity tests (test battery). The three best cell systems were selected (7), but the need for additional in vitro tests was recently outlined (8,9).…”
Section: Introductionmentioning
confidence: 99%